2018
DOI: 10.1111/pbi.13019
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous regulation of F5H in COMTRNAi transgenic switchgrass alters effects of COMT suppression on syringyl lignin biosynthesis

Abstract: Summary Ferulate 5‐hydroxylase (F5H) catalyses the hydroxylation of coniferyl alcohol and coniferaldehyde for the biosynthesis of syringyl (S) lignin in angiosperms. However, the coordinated effects of F5H with caffeic acid O ‐methyltransferase ( COMT ) on the metabolic flux towards S units are largely unknown. We concomitantly regulated F5H expression in COMT ‐down‐regulated transgenic switchgrass ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 42 publications
2
31
0
Order By: Relevance
“…Switchgrass ( Panicum virgatum L.), as a well-known bioenergy crop found on marginal lands [ 1 ], has a substantial potential to help relieve the world energy shortage [ 2 ]. It does not just have the dual purposes as a forage and energy crop [ 3 ], but it is even able to improve the aggregate stability of soil and its microbial biomass while reducing soil disturbance with a perennial rooting system [ 4 ]. Thus, since switchgrass is both an economical and environmentally friendly crop, its study and improvement merit substantial research.…”
Section: Introductionmentioning
confidence: 99%
“…Switchgrass ( Panicum virgatum L.), as a well-known bioenergy crop found on marginal lands [ 1 ], has a substantial potential to help relieve the world energy shortage [ 2 ]. It does not just have the dual purposes as a forage and energy crop [ 3 ], but it is even able to improve the aggregate stability of soil and its microbial biomass while reducing soil disturbance with a perennial rooting system [ 4 ]. Thus, since switchgrass is both an economical and environmentally friendly crop, its study and improvement merit substantial research.…”
Section: Introductionmentioning
confidence: 99%
“…However, some double mutants or transgenetically altered plants targeting two genes for downregulation, such as Arabidopsis ccoaomt1 comt1 and switchgrass hydroxycinnamoyl CoA:shikimate hydroxycinnamoyl transferase (HCT) 1 and 2, have compromised growth [22, 47], suggesting that not all mutant combinations of genes in lignin biosynthesis present practical strategies for overcoming recalcitrance. One further modification that has succeeded in returning plant growth to normal was to downregulate or overexpress other lignin-related genes or transcription factors [4850]. Such elaborate experimental approaches to modify lignin content enable the plants with reduced lignin content not only for practical biofuel-based applications but also as tools for gaining a deeper understanding of regulatory mechanisms underlying lignin biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The content of the crude protein of paper mulberry varies from 18% to 22%, which is higher than other xylophyta, such as Morus alba L. [35]. A previous study found that the lignin content and composition, especially the level of syringyl-lignin, affected the digestibility of forage [36]. Peng et al [37] found that the caffeic acid 3-O-methyltransferase gene family that affected syringyl-lignin biosynthesis expended in paper mulberry through the genome analysis.…”
Section: Discussionmentioning
confidence: 99%